2023
DOI: 10.1038/s41467-023-41463-8
|View full text |Cite
|
Sign up to set email alerts
|

Terahertz radiation by quantum interference of excitons in a one-dimensional Mott insulator

Tatsuya Miyamoto,
Akihiro Kondo,
Takeshi Inaba
et al.

Abstract: Nearly monocyclic terahertz waves are used for investigating elementary excitations and for controlling electronic states in solids. They are usually generated via second-order optical nonlinearity by injecting a femtosecond laser pulse into a nonlinear optical crystal. In this framework, however, it is difficult to control phase and frequency of terahertz waves. Here, we show that in a one-dimensional Mott insulator of a nickel-bromine chain compound a terahertz wave is generated with high efficiency via stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…Zhang et al [14] reported the design of a highly efficient THz detector incorporating a Tamm cavity, which involves an embedded detector chip within a multilayer Si/air Distributed Bragg Reflector (DBR) for significant enhancement of the strength of the THz signal. Miyamoto et al [15] applied a different approach of utilizing a 1D Mott insulator of a nickelbromine chain compound, leveraging strong electron modulation resulting from quantum interference between even and odd parity excitations to make notable strides in the efficient generation of THz waves. These advancements collectively set up a rapidly evolving landscape of THz research, contributing valuable insights and innovations to the field.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [14] reported the design of a highly efficient THz detector incorporating a Tamm cavity, which involves an embedded detector chip within a multilayer Si/air Distributed Bragg Reflector (DBR) for significant enhancement of the strength of the THz signal. Miyamoto et al [15] applied a different approach of utilizing a 1D Mott insulator of a nickelbromine chain compound, leveraging strong electron modulation resulting from quantum interference between even and odd parity excitations to make notable strides in the efficient generation of THz waves. These advancements collectively set up a rapidly evolving landscape of THz research, contributing valuable insights and innovations to the field.…”
Section: Introductionmentioning
confidence: 99%